Photodynamic therapy in root canals contaminated with Enterococcus faecalis using curcumin as photosensitizer - Frota, Matheus Franco da; Tanomaru Filho, Mario; Bagnato, Vanderlei Salvador; Espir, Camila Galetti; Berbert, Fabio Luis Camargo Villela; Tanomaru, Juliane Maria Guerreiro [UNESP] (Springer Nature, 2014)
The aim of the study was to evaluate the photodynamic therapy (PDT) effect on root canals contaminated with Enterococcus faecalis using a light emitting diode (LED) light and a curcumin solution (CUR) as photosensitizer (PS). Eighty root canals from uniradicular human teeth were prepared with Protaper Universal rotary system and contaminated with E. faecalis for 21 days. They were divided as: GIa-PDT (CUR, pre-irradiation for 5 + 5 min of irradiation); GIb-PDT (CUR, pre-irradiation for 5 + 10 min of irradiation); GIIa-(CUR, pre-irradiation for 5 + 5 min without irradiation); GIIb-(CUR pre-irradiation for 5 + 10 min of irradiation); GIIIa-(physiological solution and irradiation for 5 min); and GIIIb-(physiological solution and irradiation for 10 min); positive and negative control groups. Collections from root canals were made at time intervals of 21 days after contamination, immediately after treatment, and 7 days after treatment, and submitted to colony forming units per milliter (CFU mL-1) counts. The data were submitted to ANOVA and Tukey multiple comparison tests, at a level of significance of 5 %. In the immediate post-treatment collection, group GIa showed greater bacterial reduction in comparison with GIIa, GIIb, GIIIa, GIIIb, and positive control (P < 0.05). At 7 days post-treatment, GIa showed significant bacterial reduction only in comparison with GIIIa (P < 0.05). Curcumin as sensitizer was effective by 5 min LED irradiation but not by 10 min irradiation PDT using LED light, and curcumin as PS was not effective in eliminating E. faecalis. No difference was observed for periods of irradiation.
Keywords: Photodynamic therapy; Enterococcus faecalis; LED; Curcumin